O gênero textual crônica na aula de Língua Portuguesa: práticas de leitura e aprendizagem no ensino fundamental - Silva, Adriana Ferreira da (2023)
The act of reading is very comprehensive, as it goes beyond decoding. When you acquire the reading skill, you also understand issues necessary for social practices. The problems related to the apparent lack of interest in reading on the part of elementary school students, in the final years, have generated numerous consequences, as this gap is reflected not only in school subjects, compromising the understanding of the knowledge that is offered by the language areas, humanities and natural sciences, but mainly in the development of autonomy in social experiences. In this context, we aimed to analyze how a didactic procedure aimed at reading chronicles can contribute to the critical formation of students in the 9th grade of elementary school, at a state public school, in the city of Nova Cruz/RN. In addition to this general objective, we had the following specific objectives: to discuss what studies on reading and reading teaching say; diagnose the difficulties and reading skills of students in the face of the chronicle textual genre; develop strategies that introduce students to reading practices through the chronicle genre. As for the approach, the research is quantitative and qualitative and applied in nature. As for the procedures, we used bibliographical research and interventionist action research, with conversation circles and pedagogical workshops. As for the bibliographical research, we focused on the works of authors such as Antunes (2002, 2009), Kleiman (2016), Ferrarezi Jr and Carvalho (2017), Jouve (2002), Solé (1998), Rojo (2004, 2015), Marcuschi (2008, 2010), among others. These theorists helped us to discuss questions about reading and its teaching, in addition to thinking about the importance of working with textual genres. With regard to action research, we initially carried out a diagnostic activity, with the purpose of observing possible gaps related to the understanding of the meanings present in the worked chronicles, later, we applied intervention activities through pedagogical workshops, focusing on reading strategies that to make it possible to add linguistic, strategic and interactional knowledge. The comparison between the diagnostic activities, initial and final, showed us that there was an advance in relation to the development of reading comprehension, consequently, in the critical formation of the students involved in the process. This result was possible due to the application of pedagogical workshops mediated by conversation circles, which favored the participation and involvement of all. In the end, we created a pedagogical notebook designed for teachers who wish to work on reading the chronicle textual genre in their classrooms.